Study of the curing kinetics of synthetic and natural polyester blends - Teoh, Tze Siang (2014)
This work reports on the curing kinetics of the natural and synthetic polyester blends cured with methyl ethyl ketone peroxide (MEKP) as initiator and Cobalt Naphthenate as accelerator. Palm oil based natural polyester was produced from alcoholysis and esterification process, whereas synthetic polyester was derived from petroleum. Generally, blending of two polymers is usually required in order to have better properties than a single polymer. In recent year, much attention was paid to blending of natural and synthetic polymer due to environmental issues, lack of petroleum, poor properties of natural vegetable oil based polymers or resins. Themain objectives of this research work are to study curing kinetics and curing time of the best composition of polymer blends of natural and synthetic polyester. The kinetics curing of best composition of natural and synthetic polyester blends was studied by DSC analysis at different heating rates such as 10, 15 and 20°C/mm. The analysis was based on the exothermic peak raised due to the double bonds breaking to give crosslinked macromolecules. Additionally, the kinetics parameters for each heating rates such as activation energy, degree of conversion and number of orders were calculated based on the established method and equations. Result analysis revealed that the DSC thermogram shows one exothermic peak. The curing time of the polymer blends decreased as the composition of synthetic polyester increased from 10%wt to 40%wt. Besides, the curing time also decreased as the composition of the curing agent increased from 0.05%wt to 0.2%wt. The best drying time is 180 minutes with the composition of 27phr of natural polyester, l8phr of synthetic polyester, 30phr styrene, 20phr MEKP and 5phr of CoNp Furthermore, the glass transition temperature of the best composition of natural and synthetic polyester blends is about - 2.5°C. Moreover, the activation energy and reaction orders are decrease as the heating rates increase.